The feminist political gaze on autobiographical performance art (ex æquo, 2013)
The history of performance art merges with the feminist theories and movements, revealing a prevailing symbiotic relationship. Feminist autobiographical performance, however, is more consonant with the political dimension of what is personal, critically exploring the public / private dialectics, so significant for feminist perspectives. Therefore, we are interested in reflecting on the constancy of these relationships and how they are manifested today in order to articulate these artworks with a feminist reading and conclude about its political significance and impact, as illustrated through Carlota Lagidos artworks. This study underscores the relevance of a more intentional interconnection between activism and feminist social movements, academia and the arts, with particular emphasis on performance art.
Keywords: 1990; Autobiographical performance, feminisms, personal-political, public-private